Coping Attitudes of Cancer Patients and Their Caregivers and Quality of Life of Caregivers - Aydogan, Umit (Indian J Palliat Care, 2016)
BACKGROUNDS AND AIM: Cancer process is a traumatic period for both patients and their caregivers. Caregivers of the patients use various coping methods to minimize the effects of anxiety-creating negativities in their daily lives. The present study aimed to examine the coping attitudes adopted by the patients and caregivers and the effects of this process upon the quality of life (QoL) of caregivers. METHODS: The cross-sectional study was conducted on three groups of (i) 74 patients consisting of those hospitalized in the department of medical oncology in tertiary care hospital or coming to the health center for chemotherapy treatment as cancer outpatients and (ii) 46 caregivers of patients; and control group 46 healthy individuals. Face-to-face interviews were conducted with the study patients to administer a short sociodemographic questionnaire, coping attitudes assessment scale (COPE), and Short Form-36 (SF-36) QoL scale. RESULTS: Statistically significant differences were recorded among patients, caregivers, and control groups in terms of “problem-focused coping” and “dysfunctional coping” the COPE scale (P = 0.001, P = 0.017). According to scores taken from the SF-36 scale, there was a statistically significant difference between caregivers and control groups in all parameters (P < 0.05). CONCLUSION: Patients and caregivers should be encouraged to use the coping methods related to the source of the problem rather than the dysfunctional coping methods. Evaluation of the QoL indicators of not only the patients but also their caregivers enables to formulate a more integrated approach and detection of the expectations of the caregivers.